Thermal performance evaluation of a mineral-based cement tile as roofing material. Issue 3 (March 2017) - Kiran Kumar, D.E.V.S.; Puranik, Sanket
In tropical climates like India, solar radiation is the major source of heat gain through roofs as they are exposed to the sun throughout the day. As the ambient conditions are dynamic, it is important to look at periodic variation of heat flow through roofs. In this context, apart from U-values that the Energy Conservation Building Code of India (ECBC-2007) prescribes for envelopes, more specific performance indicators should be considered for designing energy efficient buildings. The study presented in this paper evaluates thermal performance of Cement Tile as roofing material and compares it with the performance of two other typical roof insulation materials monitored in hot and dry climate of India. The results are supported with physical structures using Scanning Electron Microscope (SEM) images and energy simulations. Despite having higher overall U-value (over six times), Model 1 (with Cement Tile) shows better thermal performance and negligible energy savings than Model 2 (with extruded polystyrene as insulation material) and Model 3 (with POP false ceiling). Therefore, the overall U-values calculated from the layer wise thermal conductivity along with Discomfort Degree Hour, Building Index, and Average heat flux would provide a better understanding of thermal performance of the roof as was demonstrated by our experiments.